Transition on the shop floor : the restructuring of a weaving mill, Hungary 1988-97 - János Köllîo (Institute for the Study of Labor (IZA), 2003)
While a variety of studies analysed the benign effects of privatisation on firm performance under post-socialist transition using financial data very little is known about how the apparent productivity gains were achieved. This paper follows a weaving mill from 1998 to 1997 on its way of becoming a capitalist enterprise and gives a detailed account of the sources and limits of productivity growth. The data suggests that the factory was not far from the competitive optimum given the size of ?plant and equipment? - efficiency gains were mostly achieved by plant size reduction and asset stripping. The gains from this sort of initial restructuring helped many former state enterprises stay on the market but they did not necessarily indicate high levels of adaptability, capacity to innovate and ability to attract outside investors. In economies with many ?seemingly restructured? privatised enterprises the elimination of the former state sector jobs is likely to continue within the private sector. The process may last for years after privatisation as a legal act had been fully accomplished.
Keywords: J31; L2; D21; 330; firm behaviour; firm objectives; compensation; transition; Hungary; Weberei; Privatisierung; Reorganisation; Technische Effizienz; Produktivität; Unternehmensentwicklung; Schätzung; Ungarn